2003
DOI: 10.1080/0307945021000071614
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequences of goose circovirus isolated in Taiwan

Abstract: We report the complete nucleotide (nt) sequences of eleven goose circovirus (GoCV) isolated in Taiwan. Nine out of the eleven isolates had a genome size of 1821 nt, whereas the remaining two isolates have a size of 1820 nt. Sequence comparisons of the eleven Taiwanese GoCV isolates and a German isolate revealed that these viruses could be divided into three distinct genetic groups. Group I contains the German isolate, group II contains three Taiwanese isolates, and group III contains eight Taiwanese isolates. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 0 publications
4
19
1
Order By: Relevance
“…Inclusion bodies were found in the cytoplasm of medulla and cortex of bursal follicular cells and bursal epithelial cells, and viral particles about 15 nm in diameter were observed. Similar clinical signs were described by Chen et al (2003). Ball et al (2004) reported that GoCV infection was determined by PCR and dot-blot hybridization in BF samples showing intracytoplasmic inclusion bodies.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Inclusion bodies were found in the cytoplasm of medulla and cortex of bursal follicular cells and bursal epithelial cells, and viral particles about 15 nm in diameter were observed. Similar clinical signs were described by Chen et al (2003). Ball et al (2004) reported that GoCV infection was determined by PCR and dot-blot hybridization in BF samples showing intracytoplasmic inclusion bodies.…”
Section: Introductionsupporting
confidence: 62%
“…The GoCV complete nucleotide sequence was then reported (Todd et al, 2001b). Another 11 complete genomes of GoCV were sequenced by Chen et al (2003) in Taiwan. Sequence alignment revealed that they could be divided into three distinct genetic groups.…”
Section: Introductionmentioning
confidence: 99%
“…The nucleotide sequences were aligned with the sequences of German and Taiwanese goose circovirus strains obtained from the GenBank (Chen et al ., 2003;Ball et al ., 2004) by BioEdit sequence alignment editor software using the Clustal W multiple alignment algorithm.…”
Section: Methodsmentioning
confidence: 99%
“…Other members of the Circoviridae family, infecting species other than domestic fowl, have also been receiving attention; for example, beak and feather disease virus in psittacines (Hess et al ., 2004;Johne et al ., 2004;Raue et al ., 2004), goose circovirus (Chen et al ., 2003a;Ball et al ., 2004;Smyth et al ., 2005) and columbid circovirus in pigeons (Soike et al ., 2001).…”
Section: Viruses Of Wild Birds and Minor Domestic Speciesmentioning
confidence: 99%